Chemotherapy for metastatic castration‐sensitive prostate cancer. (26th June 2016) - Parimi, Sunil; Chi, Kim N
Abstract: Incorporation of docetaxel into metastatic castration‐sensitive prostate cancer treatment has added a new treatment option to a disease state that had previously not seen change for decades. Early attempts of a chemo‐hormonal approach for castration‐sensitive prostate cancer were not successful. With the demonstration of survival benefits using docetaxel in patients with metastatic castration‐resistant prostate cancer, this encouraged continued research with docetaxel given earlier in the disease course. Three randomized phase III trials have defined the benefits of docetaxel in the metastatic castration‐sensitive prostate cancer setting; however, there remain questions and controversies on the appropriate and optimal patient selection.